2005
DOI: 10.1373/clinchem.2004.047241
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Isoprostane Concentrations, Metabolic Acidosis, and Morbid Neonatal Outcome

Abstract: arginine and ADMA and SDMA, respectively. The addition of l-arginine, ADMA, or SDMA did not influence the measurement of the other analytes. We also determined within-and between-run imprecision (CVs; n ϭ 10). The within-run CVs were 3.3% for l-arginine, 2.6% for ADMA, and 2.5% for SDMA. Between-run CVs were 4.7% for l-arginine, 4.1% for ADMA, and 3.9% for SDMA We also measured ADMA in plasma samples from healthy human volunteers (n ϭ 22) by this LC-MS/MS method. Shown in Fig. 1 is a typical chromatogram of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Actually, increased brain levels of 8-epi-PGF2a were found in asphyctic newborn rats 2 h after global perinatal asphyxia, and this biomarker could be predictive of delayed behavioral disturbances [22]. These biomarkers have several advantages, such as establishing a quantitative result and diagnosis to clinically undefined samples, and being potential long-term neurological damage biomarkers [14,22]. This fact can be explained by the molecular damage occurred under hypoxic episode depending on its intensity, duration, previous metabolic state, gestational age, and the degree of development of the antioxidant system, altogether these factors can induce a different response to a hypoxic episode.…”
Section: Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, increased brain levels of 8-epi-PGF2a were found in asphyctic newborn rats 2 h after global perinatal asphyxia, and this biomarker could be predictive of delayed behavioral disturbances [22]. These biomarkers have several advantages, such as establishing a quantitative result and diagnosis to clinically undefined samples, and being potential long-term neurological damage biomarkers [14,22]. This fact can be explained by the molecular damage occurred under hypoxic episode depending on its intensity, duration, previous metabolic state, gestational age, and the degree of development of the antioxidant system, altogether these factors can induce a different response to a hypoxic episode.…”
Section: Compoundsmentioning
confidence: 99%
“…The role of oxidative stress biomarkers has been reviewed [14]. In the experimental setting metabolomic studies performed in animal models of hypoxia reoxygenation have shown that oxidative stress associated metabolites strongly correlate with brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, vascular disorders of the newborn involve disturbed not only PGI 2 , TXA 2 , and PGE 2 metabolism but also changes in other eicosanoids (Ostrea et al, 2006). Isoprostanes have been associated with increased morbidity of neonatal PPHN (Gong et al, 2010), ROP (Hardy et al, 2000), and HIE (Rogers et al, 2005). On the other hand, in addition to the cytoprotective role of PGI 2 in later stages of ischemic injury associated with HIE, PGD 2 acting through DP1 receptors may protect the neonatal brain against EC degeneration (Taniguchi et al, 2007).…”
Section: Conclusion and Future Implicationsmentioning
confidence: 99%
“…25 Similarly, most reports of cord blood lipid peroxidation in fetal distress have been in term infants. 26-29 These studies also show marked variability that appears to be influenced by obstetrical intervention and mode of delivery. 30-32 Consistent with these findings in our preterm population, covariates of medical intervention (e.g., artificial ROM, tocolysis, c-section delivery) all had odds ratios <1.0 with elevated 8-IP, suggesting a protective effect.…”
Section: Discussionmentioning
confidence: 93%